Fluorescent substrates for haloalkane dehalogenases: Novel probes for mechanistic studies and protein labeling - Dockalova, Veronika; Sanchez-Carnerero, Esther M; Dunajova, Zuzana; Palao, Eduardo; Slanska, Michaela; Buryska, Tomas; Damborsky, Jiri; Klán, Petr; Prokop, Zbynek (Computational and structural biotechnology journal, 2020)
Haloalkane dehalogenases are enzymes that catalyze the cleavage of carbon-halogen bonds in halogenated compounds. They serve as model enzymes for studying structure-function relationships of >100.000 members of the α/β-hydrolase superfamily. Detailed kinetic analysis of their reaction is crucial for understanding the reaction mechanism and developing novel concepts in protein engineering. Fluorescent substrates, which change their fluorescence properties during a catalytic cycle, may serve as attractive molecular probes for studying the mechanism of enzyme catalysis. In this work, we present the development of the first fluorescent substrates for this enzyme family based on coumarin and BODIPY chromophores. Steady-state and pre-steady-state kinetics with two of the most active haloalkane dehalogenases, DmmA and LinB, revealed that both fluorescent substrates provided specificity constant two orders of magnitude higher (0.14-12.6 μM-1 s-1) than previously reported representative substrates for the haloalkane dehalogenase family (0.00005-0.014 μM-1 s-1). Stopped-flow fluorescence/FRET analysis enabled for the first time monitoring of all individual reaction steps within a single experiment: (i) substrate binding, (ii-iii) two subsequent chemical steps and (iv) product release. The newly introduced fluorescent molecules are potent probes for fast steady-state kinetic profiling. In combination with rapid mixing techniques, they provide highly valuable information about individual kinetic steps and mechanism of haloalkane dehalogenases. Additionally, these molecules offer high specificity and efficiency for protein labeling and can serve as probes for studying protein hydration and dynamics as well as potential markers for cell imaging.
Keywords: Fluorescent substrate; Haloalkane dehalogenase; Enzyme kinetics; Protein labeling; Mechanism